Makna kewirausahaan pada etnis Jawa, Minang, dan Tionghoa: Sebuah studi representasi sosial - Sutanto, Okki; Nurrachman, Nani (Konsorsium Psikologi Ilmiah Nusantara, 2018)
The important link between culture and entrepreneurship has often been overlooked by psychological research on entrepreneurship. The present study explores the meaning of entrepreneurship among three ethnic groups in Indonesia: Javanese, Minangese, and Chinese. Using the perspective of social representation theory, especially the structural approach, this study employs the mixed-method design. By using quantitative approach with Hierarchized Evocation method on 122 subjects the attributes and structure of entrepreneurship’s social representation were discovered. The central core elements of the Javanese were autonomy and hard work, the Minangese were trading, products, capital, and autonomy, and for the Chinese were strategy and management and hard work. The qualitative approach using interview conducted on 11 entrepreneurs found that each ethnic group views entrepreneurship differently. The different views manifested on several aspects such as the motivation to start a business, the important values and views regarding entrepreneurship. Some attributes which were found to be unique for each ethnic were honesty and nrimo for the Javanese, observance to religion and belongingness to one’s hometown for the Minangese, and creativity and patience for the Chinese.